Japan's new arms export policies: strategic aspirations and domestic constraints. Issue 6 (1st November 2020) - Sakaki, Alexandra; Maslow, Sebastian
ABSTRACT: This article examines the significance of the changes in Japan's arms export policy following Prime Minister Abe Shinzō's return to power in 2012—a topic which has so far received insufficient scholarly attention. Established in the 1960s and 1970s, Japan's 'virtual' ban on arms exports was an expression of the country's postwar anti-militarism. Yet, in keeping with Japan's increasingly active role in security affairs, Abe lifted the ban on weapons exports in 2014. Within the Ministry of Defense, a new agency was installed to oversee the arms industry and to promote military-related research and weapons transfers. We show that the Abe administration conceives of arms exports and related cooperation as an integral part of its national security strategy. Tokyo not only hopes to improve the competitiveness of its own defence industry, but also seeks to cement existing and new security partnerships while contributing to regional capacity building as a hedge against a rising China. The actual ramifications of this policy change are far from clear yet, however. A major constraint for policymaking is the reluctance of the defence sector to embrace arms export due to the associated business risks including the fear of tarnishing their corporate image.